Synthesis of polyethersulfone ultrafiltration membranes with different molecular weights polyethylene glycol as additives [electronic resource] - 363653 Norashikin Mat Zain (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2006